2001
DOI: 10.1097/00007890-200105270-00004
|View full text |Cite
|
Sign up to set email alerts
|

Heart Preservation With Celsior Solution Improved by the Addition of Nitroglycerine 1

Abstract: Celsior was not as effective as MUW for rat heart preservation. The addition of NTG to both CEL and MUW provided similar effective preservation for 16 hr. NTG should be added routinely to both solutions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…Consistent with a previous report, no heart grafts survived Ͼ7 days when the grafts were stored in Celsior solution for 18 hours prior to transplantation if the recipients received no therapeutic gas. 19 Although only 10% of the recipients survived Ͼ7 days after receiving CO treatment, dual therapy and hydrogen therapy alone significantly enhanced graft survival as compared with no treatment. Most strikingly, graft survival of Ͼ7 days was seen in 90% of the recipients receiving dual-gas therapy ( Figure 2F).…”
Section: Dual Treatment With Hydrogen and Co Had A Protective Effect mentioning
confidence: 97%
“…Consistent with a previous report, no heart grafts survived Ͼ7 days when the grafts were stored in Celsior solution for 18 hours prior to transplantation if the recipients received no therapeutic gas. 19 Although only 10% of the recipients survived Ͼ7 days after receiving CO treatment, dual therapy and hydrogen therapy alone significantly enhanced graft survival as compared with no treatment. Most strikingly, graft survival of Ͼ7 days was seen in 90% of the recipients receiving dual-gas therapy ( Figure 2F).…”
Section: Dual Treatment With Hydrogen and Co Had A Protective Effect mentioning
confidence: 97%
“…In this study, we chose to combine cariporide with GTN for a number of reasons. GTN is already widely used in clinical medicine, it has been shown to be cardioprotective in previous heart transplant studies (32,33) (34). The significance of this finding is uncertain, but Budrikis and colleagues (34) reported that the intensity and duration of early reactive hyperemia after ischemic storage was related to the extent of preservation injury in an isolated blood-perused porcine heart model.…”
Section: In This Study Lvsw After Transplantation In the Presence mentioning
confidence: 99%
“…Chloride ions are free to enter the cell at low temperatures and accumulate within the cytoplasm. 31 The net effect of these processes is an increase of intracellular solute, with water entering the cell down an osmotic gradient resulting in intracellular oedema. 28 Intracellular oedema has been associated with distortion and rupture of structural components.…”
Section: Ion Homeostasismentioning
confidence: 99%
“…31,51 Cariporide is a potent antagonist of the Na + -H + exchange, 29 and has a potent protective effect when added to cardioplegic solutions experimentally. In the GUARDIAN trial the benefit of its use in coronary artery bypass surgery was established in reducing non-Q wave MI incidence from 7.1 to 3.8%.…”
Section: Improved Ion Homeostasismentioning
confidence: 99%